2015
DOI: 10.1590/1678-457x.6834
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced extraction of phenolic compounds from coffee industry’s residues through solid state fermentation by Penicillium purpurogenum

Abstract: The use of agroindustrial residues is an economical solution to industrial biotechnology. Coffee husk and pulp are abounding residues from coffee industry which can be used as substrates in solid state fermentation process, thus allowing a liberation and increase in the phenolic compound content with high added value. By employing statistical design, initial moisture content, pH value in the medium, and the incubation temperature were evaluated, in order to increase the polyphenol content in a process of solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 32 publications
(33 reference statements)
1
8
1
1
Order By: Relevance
“…It was observed that the microorganisms acted synergistically in the production of the enzymes, with low gaseous emissions and reduced energy requirements making the bioprocess more environmentally friendly. García et al [36] cultivated Penicillium purpurogenum in plastic bags, using coffee husks and coffee pulp as substrates, with the addition of sterilized cheese whey as a supplementary source of fermentable sugars (4.5-5.0% lactose), aiming at the extraction of total phenolic compounds. The coffee industry wastes supplemented with cheese whey were appropriate substrates for the growth of the microorganism and for obtaining phenolic compounds by the action of the enzymes produced during the process.…”
Section: Comparison Of the Types Of Cultivation Under Ssfmentioning
confidence: 99%
“…It was observed that the microorganisms acted synergistically in the production of the enzymes, with low gaseous emissions and reduced energy requirements making the bioprocess more environmentally friendly. García et al [36] cultivated Penicillium purpurogenum in plastic bags, using coffee husks and coffee pulp as substrates, with the addition of sterilized cheese whey as a supplementary source of fermentable sugars (4.5-5.0% lactose), aiming at the extraction of total phenolic compounds. The coffee industry wastes supplemented with cheese whey were appropriate substrates for the growth of the microorganism and for obtaining phenolic compounds by the action of the enzymes produced during the process.…”
Section: Comparison Of the Types Of Cultivation Under Ssfmentioning
confidence: 99%
“…Arabica coffee ground nanoparticles have a phenolic content of 1246.897 µg GAE/g. The phenolic compounds in coffee have some bioactivities, such as antioxidant, antibacterial and anti-inflammatory activities [29,30,32,33,[41][42][43]. The total phenolic dosage of the coffee ground nanoparticles gel preparations ranged from 540.86 to 672.10 µg GAE/g ( Table 2).…”
Section: Total Phenolicmentioning
confidence: 99%
“…The lowest TPC (2.53 mg GAE/g) and % of radical scavenging activity (10.10%) was obtained at 0 days; temperature, 32°C; initial moisture content, 80% and inoculum level, 10% (v/v), respectively. Initial moisture content between 50 -75% is the best condition to increase phenolic compounds in coffee residues when fermented with Penicillium purpurogen [14]. Previous researchers reported that antioxidant activity was correlated well with total phenolic content, suggesting that polyphenols have a major influence in the antioxidant activity [15; 16].…”
Section: Optimization Of Total Phenolic Content (Tpc) and Dpphmentioning
confidence: 99%